Effectiveness of Module on Knowledge and Practice Regarding Prevention of Medication Errors among Critical Care Nurses in Selected Hospital - Jeba B1 , Jasneet Kaur2 , Deepak Sethi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction and objective: Medication administration is the major tasks of each nurses in their clinicalpractice. Medication administration errors are preventable if the nurses have adequate knowledge andpractices regarding the medications. Hence the main objective of this study was to determine the effectivenessof module on knowledge and practices regarding prevention of medication errors among critical care nurses.Methodology: Pre experimental one group pretest and posttest research method used for the study. 50critical care nurses were selected using convenient sampling method and given questionnaire to assess theirknowledge in pretest and posttest done after 1week of intervention. Checklist used to assess their practicesin pretest and posttest.Result: The mean score of knowledge in pre-test was 13.2 and in post-test was 21.5 and the t-value was 27.7The p value was less than 0.05. The mean score of practice in pre-test was 35.3 and in post-test was 48.0,and the t value was 55.3 The p value was less than 0.05. This shows that the module is effective. Hence thenull hypothesis is rejected.Conclusion: The improvement found in the post test proved that the module is effective in improving theknowledge and practices regarding prevention of medication errors among critical care nurses.